2020
DOI: 10.4269/ajtmh.20-0132
|View full text |Cite
|
Sign up to set email alerts
|

No Evidence of Acute Dengue Virus Infections at a Rural Site in Western Kenya, 2011 and 2013

Abstract: The incidence and spread of dengue virus (DENV) have increased rapidly in recent decades. Dengue is underreported in Africa, but recent outbreaks and seroprevalence data suggest that DENV is widespread there. A lack of ongoing surveillance limits knowledge about its spatial reach and hinders disease control planning. We sought to add data on dengue distribution in Kenya through diagnostic testing of serum specimens from persons with an acute febrile illness (AFI) attending an outpatient clinic in rural western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…29 From where the mosquitoes travelled passively to nearby areas and ultimately Asia and Australia. 30 As the Aedes populations of Swat and Peshawar were linked closely with Asian countries, especially India, we can propose that they travelled Pakistan (Lahore) from India via trade. From Lahore the mosquitoes travelled passively to Swat, most probably in the luggage of travelers as high similarities as the sequences were clustered in the same group.…”
Section: Discussionmentioning
confidence: 99%
“…29 From where the mosquitoes travelled passively to nearby areas and ultimately Asia and Australia. 30 As the Aedes populations of Swat and Peshawar were linked closely with Asian countries, especially India, we can propose that they travelled Pakistan (Lahore) from India via trade. From Lahore the mosquitoes travelled passively to Swat, most probably in the luggage of travelers as high similarities as the sequences were clustered in the same group.…”
Section: Discussionmentioning
confidence: 99%
“…In other settings, the epidemiology of DENV infection is changing, with reports indicating a global rise in rural infections, particularly in Africa [10,26]. Conversely, in Gabon, a study suggested minimal DENV infection circulation in rural areas [27], and in Kenya a study reported no evidence of DENV infection circulation in rural communities [28].…”
Section: Introductionmentioning
confidence: 99%